Psychometric properties of a Saudi Arabian version of the Birth Satisfaction Scale-Revised (BSS-R) - Juliana Linnette D'Sa; Ibtesam Omar Jahlan; Eman S. Alsatari; Sahar Zamzam; Colin R. Martin (Belitung Nursing Journal, 2024)
Background: Maternal outcomes are closely associated with birth satisfaction, and the Birth Satisfaction Scale-Revised (BSS-R), a concise, multidimensional self-report measure, has undergone translation and validation internationally. However, research on birth satisfaction in Saudi Arabia is scarce. The absence of valid Arabic-language tools for the Saudi population may impede critical research on this topic, necessitating the translation and use of psychometrically sound instruments for measuring birth satisfaction in Saudi women. Objective: This study aimed to translate and evaluate the psychometric properties of the Saudi Arabian version of the BSS-R (SA-BSS-R). Methods: A total of 218 Saudi women participated in the study, and psychometric analysis of the translated SA-BSS-R involved confirmatory factor analysis, divergent validity analysis, and known-group discriminant validity assessment within a cross-sectional study design. Results: The three-factor BSS-R measurement model displayed poor fit, and internal consistency fell below the threshold value. Additionally, it was observed that women undergoing an episiotomy had significantly lower overall SA-BSS-R scores. Conclusion: The SA-BSS-R manifested atypical measurement properties in this population. Despite insightful observations related to episiotomy, the identified measurement shortcomings highlight the need for a more robust and culturally sensitive translation to enhance measurement characteristics.